Assessing the social factors of place dependence and changes in land use in sustainable agriculture: Case of Pandaan District, Pasuruan Regency, Indonesia - Gunawan Prayitno; Wara Indira Rukmi; Muhammad Iqbal Ashari (Publisher of Widyagama University of Malang (UWG Press), 2021)
Times have led to changes in land functions and changes in environmental psychology's social, economic, and environmental aspects. Within Pandaan sub-district, there is a main road linking Surabaya and Malang to the road hierarchy as a national arterial road, and the Gempol-Pandaan toll road has changed the function of agricultural land, particularly in Durensewu and Plintah Village. This study aims to determine the land conversion that occurs in the Pandaan District by knowing the place dependence and the relationship between the place dependence and the residents' decision to change land use. The analytical method used is the analysis of land-use change, the analysis of place dependence, and the relationship between place dependence and land-use change. Based on the results of the analysis, it is known that there is an indirect and positive relationship between place dependence and land-use change in the Pandaan District and that one of the dimensions of place dependence is environmental quality. The decision to change the land is connected to sustainable agriculture.JEL Classification: R11; R52; Q15